The Long-term Contribution of Phosphorus from Agricultural Lands to Lake Okeechobee - Vimala D. Nair; Myrlène Chrysostome; Willie G. Harris (EDIS)
This 7-page fact sheet uses a new procedure to evaluate the soil from active and abandoned dairies in the Lake Okeechobee watershed to determine their potential to negatively impact water quality through phosphorus release. Written by V.D. Nair, M. Chrysostome, and W.G. Harris, and published by the UF Department of Soil and Water Science, October 2011.